INCLINATION TOWARDS ERCP: NEED TO STICK TO THE BASICS OF GASTROENTEROLOGY - Khan, Jibran Umar Ayub; Zahir Shah, Azhar; Qaisar , Ayesha (Journal of Ayub Medical College Abbottabad, 2023)
Endoscopic retrograde cholangiopancreatography is an advanced investigation both diagnostically and therapeutically. It does need expertise and simultaneously a complete setup with the appropriate equipment, staff and radiological backup.1 The choice of the patients has to be spot on as the procedure does come up with complications like any other one including post-ERCP pancreatitis that can be bothersome to treat and challenging even for experienced gastroenterologists.2 The hospital stay is much longer sometimes with patients needing more scrutiny by the attending physician as resultant cholangitis is very troublesome and agonising for the patient needing antibiotics. 2The rising fever and increase in inflammatory markers take days to settle. . So prevention is better than cure in a sense that misery of both the patient and doctor can be avoided. It's a common observation that most young gastroenterologists are more inclined towards learning ERCP.3 This is very encouraging keeping in mind there is a deficiency of skills, especially in peripheries. The problem is that eagerness to learn such advanced procedures has kept them out of the loop and rather deviated them from the basics of gastroenterology and hepatology because they tend to forget the theoretical knowledge and core concepts which are inevitably essential prerequisites for an emerging expert.2 Most ERCPS is done after a detailed workup and as a follow-up the investigation after magnetic resonance pancreatography, (MRCP) which is a non-invasive investigation for finding the cause of deranged liver function and dilated common bile duct on ultrasound abdomen for gallstones.4 Its better not to rely on a single US abdomen report if the clinical picture is different. It's more appropriate to repeat it and go for an ERCP if the situation demands .This all comes with experience after seeing so many patients presenting with different forms and manifestations. The biggest dilemma is that most of the specialists do ERCPs directly without doing non-invasive investigations and that is when the clinical judgement of a physician is compromised and there is an increased risk of complications such as pancreatitis and perforation. The overall risk of PEP risk is 9.7% which can rise to over 14.7% in high-risk patients especially those with sphincter of Oddi dysfunction and a previous history of pancreatitis.5 It's a better and safer approach to weigh the benefits vs. complications. Merely complications and giving reasons aren't enough. One needs to own them as well by managing on time and counselling the patients why did they happen in the first place as there is element of colossal trust between the patient and attending physician that need to be kept As gastroenterologists we struggle with simple interpretation of deranged liver function tests rarely making wrong diagnosis by going for fancy investigations acquired from the books. There is lack of thought and wisdom at same time resulting in wastage of time and resources. The thing which arouses our curiosity is therapeutics and interventional endoscopies all the time. That shouldn't be the aim all the time though necessary for progression of our careers. There are so many other aspects of gastroenterology that we need to focus. EASL guidelines of management of hepatitis B and C are published quite frequently. 6Every year there is an update on other diseases as well such as Barret Esophagus and Gastroesophageal Reflux Disease.7 There are innovative articles reflecting the latest trends in gastroenterology published all the time. One needs to focus on reading them and acquire the basics of subject before advancing and applying them in real clinical scenarios. These scenarios are quite tricky when it comes to diagnosis and same is the case in post graduate exams with trainees failing them quite frequently .There has to be more emphasis on ward rounds and learning from scenarios in case based discussions. Simulation is a powerful learning method in medical education that can be used in clinical settings.8Similarly one has to observe the procedures,assist,perform under supervision and then doing them independently once your mentor is confident enough about the skills acquired over the period of time. There are many areas of our subject on which we need to focus ranging from acute hepatitis to hepatocellular carcinoma.9 What we need to realise is that ERCP and EUS are advanced aspects of gastroenterology but that isn't the end of the journey or the road. The eyes can't see what the mind doesn't know. There needs to be greater emphasis on the basics of gastroenterology enabling us to diagnose the patients promptly and refer the right ones for endoscopy, colonoscopy, endoscopic ultrasound, fibro scan, liver biopsy and even ERCP.10 Learning skills in a state of art of facility is must but one has to have a solid theoretical knowledge and application of it into appropriate clinical situation requiring sound clinical reasoning, critical thinking and problem solving skill.11 There are no shortcuts to experience and no stop to learning as well. It's worth learning in a good setup with compassionate seniors and letting the time teach you the best. Hard work is the key to success and learning can't be overnight. One has to be devoted to a cause as that is always rewarded and people working strenuously and continuous are winners eventually .The important thing is patience which most of us lack. All excellent clinicians were not made in a single day. They too went through the process of learning just like us .Some of us learn faster than others which shouldn't matter as slow and steady wins the race. No book or can teach you practical skills and vice versa. The skills have to be learnt properly as today you are a trainee and in future a fully fledged supervisor training so many residents. There is always a ray of hope and lightening at the end of the tunnel. As long as there is a desire and eagerness to learn from others, it will bear fruits of learning in the long run. It's wiser not to get disappointed on a single mistake in any procedure including ERCP as long you learn from that by analysing it carefully with an intention and a strong will not to repeat in future.